Protecting Educators: A Scoping Review of Interventions That Address Teacher Victimization - Sarah M. Stilwell; Paulina Guzmán; Jorge Varela; Susan D. McMahon; Kailyn Bare; Justin Heinze; Marc Zimmerman (Behavioral Sciences)
The prevalence of teacher-directed violence has been well-documented around the world. However, interventions focused on the prevention of teacher victimization have received less attention. Understanding how to reduce teacher-directed violence is vital to preserving the overall well-being of teachers, supporting their teaching, reducing teacher burnout, and providing recommendations for future research. The current scoping review reports on teacher-directed violence interventions in K–12 school settings (n = 2). In addition, emerging evidence is described that provides recommendations for developing teacher-directed violence interventions (n = 6). The results from this scoping review reinforce the need for further study of teacher victimization-focused interventions to support the essential work of teachers.